2016
DOI: 10.1111/nmo.12852
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers to distinguish functional constipation from irritable bowel syndrome with constipation

Abstract: Treatments for functional constipation (FC) and irritable bowel syndrome with constipation (IBS-C) differ, but symptom criteria do not reliably distinguish between them; some regard FC and IBS-C as parts of a single constipation spectrum. Our goal was to review studies comparing FC and IBS-C to identify possible biomarkers that separate them. A systematic review identified 15 studies that compared physiologic tests in FC vs IBS-C. Pain thresholds were lower in IBS-C than FC for 3/5 studies and not different in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 46 publications
1
17
0
1
Order By: Relevance
“…It has previously been demonstrated that the increased fiber gap of FCQS facilitates the improved penetration of water to the fibers and increases its absorbency and water-holding capacity, which increases the volume of excrement that stimulates intestinal peristalsis (17). Furthermore, increased water content in excrement may prevent dry excrement, which increases bowel movements (18). Previous research has demonstrated that fermentation can significantly improve the water-holding ability of bamboo (10), which was confirmed in the present study.…”
Section: Discussionsupporting
confidence: 78%
“…It has previously been demonstrated that the increased fiber gap of FCQS facilitates the improved penetration of water to the fibers and increases its absorbency and water-holding capacity, which increases the volume of excrement that stimulates intestinal peristalsis (17). Furthermore, increased water content in excrement may prevent dry excrement, which increases bowel movements (18). Previous research has demonstrated that fermentation can significantly improve the water-holding ability of bamboo (10), which was confirmed in the present study.…”
Section: Discussionsupporting
confidence: 78%
“…However, in deference to new data showing a strong overlap between functional constipation and irritable bowel syndrome with constipation (IBS-C) [15••, 34, 35], the Rome IV criteria state that the patient may fulfill this criterion by meeting symptom criteria for either functional constipation or IBS-C.…”
Section: Functional Defecation Disordersmentioning
confidence: 99%
“…In fact only small changes, detailed below, were made in the IBS diagnostic criteria. In part, they were made to address important questions that have been raised about (1) the inclusion of abdominal 'discomfort' as an alternative to pain [2], (2) the most appropriate frequency of pain for IBS classification, and (3) the way Rome III dealt with the comorbidity of constipation-predominant IBS (IBS-C) with functional constipation [3,4]. It is also important to update clinicians on the explosion of new information on the pathophysiology of IBS (e.g.…”
Section: Why Revise the Rome III Criteria Now?mentioning
confidence: 99%